Stories about childbirth and violence (Research, Society and Development, 2026)
The present article presents the results of a research done with the intention to reinforce and constitute the debate on Obstetric Violence (V.O.), based on the perception of women who have already experiencied childbirth. The research question arose from the search for the phenomenon of obstetric violence in a health region in the interior of Minas Gerais. To understand it, narrative research was chosen, focusing on collaboration between interviewer and interviewee, understanding that women who had experienced hospital childbirth could, based on their stories, highlight the issue and its impacts, as well as have a space to express their own questions. The results showed that women who had hospital births in this region reported situations that pointed to neglected rights, even with Brazilian government initiatives, such as the Comprehensive Women's Health Program and the Prenatal and Birth Humanization Program, reinforcing the need for a specific law on obstetric violence so that actions can be taken regarding the prevention, awareness, and identification of this violence by Brazilian women, institutions, and professionals who provide care during their deliveries. In conclusion, this research, conducted between September 2024 and August 2025, confirmed the presence of obstetric violence as a phenomenon that still occurs during childbirth.